2012
DOI: 10.1029/2012ja017835
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of plasma irregularity growth in the cusp ionosphere

Abstract: The Investigation of Cusp Irregularities (ICI‐2) sounding rocket was launched on 5 December 2008 from Ny‐Ålesund, Svalbard. The high‐resolution rocket data are combined with data from an all‐sky camera, the EISCAT Svalbard Radar, and the SuperDARN Hankasalmi radar. These data sets are used to characterize the spatial structure ofFregion irregularities in the dayside cusp region. We use the data set to test two key mechanisms for irregularity growth; the Kelvin‐Helmholtz (KH) and gradient drift (GD) instabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 77 publications
3
92
0
Order By: Relevance
“…In this study, only the linear growth rate of GDI was considered. Even though radar backscatter power and occurrence trends are often interpreted using the GDI growth rates in the linear regime (e.g., Oksavik et al, 2012;Moen et al, 2012), there are other factors that may affect echo power and occurrence. In the polar cap, HF radars rely on beam refraction through a dense ionosphere to observe field-aligned irregularities (Bristow et al, 2011;Koustov et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only the linear growth rate of GDI was considered. Even though radar backscatter power and occurrence trends are often interpreted using the GDI growth rates in the linear regime (e.g., Oksavik et al, 2012;Moen et al, 2012), there are other factors that may affect echo power and occurrence. In the polar cap, HF radars rely on beam refraction through a dense ionosphere to observe field-aligned irregularities (Bristow et al, 2011;Koustov et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…By using electron density measurements from this rocket experiment, Moen et al [] estimated the linear growth rate of the GDI process and claimed that meter‐scale irregularities in the cusp can be produced very quickly through the GDI process. Oksavik et al [] carried out more rigorous test of the GDI process as a generation mechanism of cusp irregularities and obtained similar results. In addition, Moen et al [] clearly demonstrated that kilometer‐scale density perturbations are first created by the structured soft particle precipitations in the cusp and subsequently the GDI process breaks these irregularities down to meter scales.…”
Section: Introductionmentioning
confidence: 82%
“…As mentioned above, we assume zero neutral wind in the calculation of the linear growth rate, which is, of course, not always the case. As pointed out in Oksavik et al [], the neutral wind speed in the F region polar cap may reach 60% of the ion drift speed during extended intervals of southward IMF [ Heelis et al , ]. If the neutral wind speed is 60% of the plasma flow speed, the growth rate will be reduced by a factor of 0.4 for the collisional case; thus, the corresponding growth time will increase by a factor of 2.5.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations